FORMULASI SABUN CUCI TANGAN CAIR DENGAN KOMBINASI EKSTRAK KOPI ROBUSTA (Coffea Canephora) NGEBEL PONOROGO: Formulation of Liquid Hand Wash Soap with The Addition of Robusta Coffee Extract (Coffea Canephora) Ngebel Ponorogo - Wendianing Putri Luketsi; Akbar Harun Wicaksono; Devi Urianty Miftahul Rohmah (Universitas Darussalam Gontor, 2022)
Robusta coffee contains antiseptic substances, namely caffeine, phenols and volatile acids. Caffeine has an important role in the development of immune resistance, while the phenol content has been verified to have bacteriostatic and bactericidal properties as an antiseptic, virus, and fungus. Volatile acids have activities that increase the inhibition of bacterial growth. The purpose of this study was to determine the formulation of antiseptic liquid hand soap from Ngebel Ponorogo robusta coffee (Coffea canephora) extract. This research method used was an experimental design (true experimental laboratory), with a completely randomized design (CRD) and theoretically analyzed including; organoleptic test with criteria (color, texture, aroma and foam), pH, and free alkali and statistically analyzed using software data processing with One-way ANOVA method with 95% significance (α= 0.05). The results revealed that the best formulation for organoleptic testing was F3 with a concentration of 18%, according to the results on the formulation antiseptic handwash soap Robusta Coffee (C.canephora) extract. The best result for free alkali test was F3 with a result of 0.00196. However, it failed to fulfill Indonesian Standard of liquid hand wash soap SNI 2588:2017